An environment-sensitive fluorescent probe for quantification of human serum albumin: Design, sensing mechanism, and its application in clinical diagnosis of hypoalbuminemia. (May 2018) - Luo, Zijie; Liu, Bin; Zhu, Kangning; Huang, Yingying; Pan, Chengjun; Wang, Bingfeng; Wang, Lei
Abstract: Unusual human serum albumin concentration in serum or urine represents an important early biomarker for various medical conditions and diseases. Therefore, accurate quantification of HSA concentration in real biological samples has gained great importance for clinical diagnosis and preventive medicine. However, most of previous reports focus on detection of serum samples collected from healthy individuals, rather than the patients with abnormal serum albumin level. Further validation of HSA probes in clinical diagnosis is urgently needed yet remains challenging. Here, we reported an environment-sensitive fluorescent probeCD1, which exhibited fast response, high sensitivity, and excellent selectivity towards HSA. The limit of detection was determined to be as low as 8.6 nM (0.57 mg/L). Based on this method, the quantitative determination of HSA in real serum samples from both healthy individuals and patients with hypoalbuminemia are firstly reported, which demonstrated its practical application in clinical disease pre-diagnosis. Highlights: Highly sensitive and selective detection of human serum albumin with a detection limit of 8.6 nM. Investigation of sensing mechanism by molecular docking techniques. Quantification of human serum albumin in real serum samples. Clinical diagnosis of hypoalbuminemia with high accuracy.